1975
DOI: 10.1139/v75-268
|View full text |Cite
|
Sign up to set email alerts
|

Horseradish Peroxidase. XVIII. The Arrhenius Activation Energy for the Formation of Compound I

Abstract: The rate of formation of compound I from the reaction of native horseradish peroxidase with hydrogen peroxide was studied from 3.7–70.0 °C. The second-order rate constants were used to construct an Arrhenius plot from which the activation energy of this reaction was calculated to be 3.5 ± 1.0 kcal/mol. The irreversibility of the reaction at 25 °C was confirmed by comparing absolute absorbance changes as recorded by the stopped-flow apparatus with the known spectra of the native enzyme and compound I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 8 publications
3
13
0
Order By: Relevance
“…The apparent second-order rate constant we obtained, (1.8 ± 0.1) X 107 M-1 s-1, is comparable to values previously reported: (1.0 ± 0.2) X 107 M~'s-1 for rat chloroma peroxidase (Newton et al, 1965); 2.0 X 107 M-1 s-1 for canine pus myeloperoxidase (Harrison, 1976); and 2.3 X 107 M-1 s_1 for human granulocyte myeloperoxidase (Bolscher & Wever, 1984). The rate of myeloperoxidase compound I formation is also the same as that for compound I formation of horseradish peroxidase (Hewson & Dunford, 1975).…”
Section: Time (Min)supporting
confidence: 65%
“…The apparent second-order rate constant we obtained, (1.8 ± 0.1) X 107 M-1 s-1, is comparable to values previously reported: (1.0 ± 0.2) X 107 M~'s-1 for rat chloroma peroxidase (Newton et al, 1965); 2.0 X 107 M-1 s-1 for canine pus myeloperoxidase (Harrison, 1976); and 2.3 X 107 M-1 s_1 for human granulocyte myeloperoxidase (Bolscher & Wever, 1984). The rate of myeloperoxidase compound I formation is also the same as that for compound I formation of horseradish peroxidase (Hewson & Dunford, 1975).…”
Section: Time (Min)supporting
confidence: 65%
“…Compound I Formation Rate and Effect of Chelators. The primary reaction product of peroxidases with H2O2 is the oxidized intermediate compound I. MnP compound I is similar to other peroxidase compounds I in its spectral features and in the activation energy for its formation (Wariishi et al, 1988(Wariishi et al, ,1989Dunford & Stillman, 1976;Renganathan & Gold, 1986;Marquez et al, 1988;Hewson & Dunford, 1975;Andrawis et al, 1988;Job etal., 1978). We have shown that the second-order rate constant for MnP compound I formation with H2O2 as the substrate is independent of pH over the range 3.1-8.3 (Wariishi et al, 1989).…”
Section: Discussionmentioning
confidence: 92%
“…The apparent activation energy for the formation of compound I of native HRP has been reported to be 14.7 ± 4.2 kJ mol Ϫ1 . 30 The corresponding energy for the formation of MnHRP᎐I is slightly higher for all the peroxides (see Table 2). The minimum theoretical energy of activation for a reaction in water (E act water ) has been found to be 16.3 kJ mol Ϫ1 , 31 which is lower than the energy of activation reported for the formation of HRP᎐I.…”
Section: Discussionmentioning
confidence: 95%